Understanding the Evolution of Mitochondrial Genomes in the Green Macroalgal Genus Ulva (Ulvophyceae, Chlorophyta) - Liu, Feng; Melton, James T.; Wang, Hongshu; Wang, Jing; Lopez-Bautista, Juan M. (Frontiers in Marine Science, 2022)
To gain more insights into the evolution of mitochondrial genomes (mitogenomes or mtDNAs) in the green macroalgal genus Ulva (Ulvophyceae, Chlorophyta), we sequenced seven Ulva mitogenomes from six species as well as one Percursaria mitogenome as outgroup, and compared them with the available Ulva mtDNA data. Our comparative analyses unveiled many novel findings. First, the Ulva mitogenomes shared a total of 62 core genes including 29 protein-coding genes (PCGs), three ribosomal RNA genes (rRNAs), 26 transfer RNA genes (tRNAs), three conserved free-standing orfs, and one putative RNA subunit of RNase P (rnpB). The rrn5 gene previously unrecognized is present in all sequenced ulvalean mitogenomes, which is situated between trnG(ucc) and trnW(cca). Second, the evolution of tRNAs in Ulva mitogenomes is related to different processes, including duplication, transposition, remolding, degeneration, loss and recruitment of tRNAs. The duplication of three tRNAs, i.e. trnT1(ugu), trnI1(gau) and trnM2(cau), was observed in Ulva mitogenomes. Third, the DNA-directed RNA polymerases (rpos), belonging to single-subunit DNA-dependent RNA polymerase (ssRNAP) family, are common in ulvalean mitogenomes. A toal of three full-length and 55 split rpos have been detected in these 33 ulvalean mitogenomes. Fourth, six types of group I/II introns are detected at 29 insertion sites which are related to seven host genes (atp1, cox1, cox2, nad3, nad5, rnl and rns) in these ulvalean mitogenomes. One group IB intron, i.e. intron cox1-214 which carried a GIY-YIG homing endonuclease (GHE), was observed for the first time in Ulva organelle genomes. Finally, phylogenomic analyses based on mitogenome dataset showed that the Ulva was split into two sister clades, repesenting Ulva lineage I and II, which was consistent to the results based on plastid genome dataset. Our study provides more important findings to better understand the evolution of mitochondrial genome in green algae.